Delirium with Concurrent Use of Lithium and ECT and the Safety Implications: Case Reports and Review of the Literature - Mustafa Ali; Barikar C. Malathesh; Seshadri Sekhar Chatterjee; Soumitra Das; Prakriti Pokhrel; Mary Elizabeth Trejo Hernandez; John C. Murnin (Case Reports in Psychiatry)
Using electroconvulsive treatment and lithium together to treat acute manic episodes is common, but the effects of combining these therapies vary according to the literature. Some studies have found severe adverse side effects, while others have found the combination of both medications safe and helpful. To investigate potential adverse side effects, this study reports on two cases where bipolar affective disorder patients developed delirium after receiving electroconvulsive therapy and lithium concurrently. The delirium was attributed only to the combined administration of these medicines after ruling out other potential causes. Additionally, alterations in blood-brain barrier permeability, such as those caused by electroconvulsive therapy and age, increased the likelihood of delirium. As a result, caution should be taken when using this combination of medicines, especially in those predisposed to delirium. This study established links between these medications and adverse effects, such as delirium. Further research is necessary to determine the efficacy and risks of combining these medications, establish causality, and develop prevention strategies.